Anxiety and Depression in Patients with Coronary Artery Disease - SARI, İBRAHİM; SÜNBÜL, MURAT (KURE ILETISIM GRUBU A S, 2013)
Objective: Previous prospective studies have reported depression as an independent risk factor for myocardial infarction and cardiovascular mortality. Anxiety disorders are also known to be associated with coronary artery disease (CAD. Psychological factors may also affect the course and outcome of CAD through behavioral mechanisms such as smoking, decreased physical activity, poor diet, and reduced compliance to treatment. The aim of this study was to explore the anxiety and depression levels and to determine the atherosclerotic risk factors in patients admitted for elective coronary angiography due to suspected CAD. Methods: The study population consisted of 116 patients, who were consecutively admitted for elective coronary angiography. Findings were classified into two major groups: normal or abnormal coronary angiography. Abnormal coronary angiography was suggested in patients with atherosclerotic disease (equal to or greater than 50% stenosis) and/or slow blood flow in coronary arteries. Anxiety and depression symptom severities were assessed by self-reported scales, including the Beck Depression Inventory, Beck Anxiety Inventory and Spielberger's State-Trait Anxiety Inventory. Results: Sixty-three patients (44 male, mean age: 52.2 +/- 11.1 years) had abnormal coronary angiography while fifty-three patients (40 male, mean age: 54.5 +/- 10.5 years) had normal findings. Sociodemographic characteristics and atherosclerotic risk factors were similar for both groups. Patients with abnormal coronary angiography had significantly higher depression and anxiety scores compared to patients with normal coronary angiography. In logistic regression analyses, only a Beck Anxiety Inventory score over 15 (odds ratio: 13.2, CI: 3.8-46.4) and State-Trait Anxiety Inventory score over 42 (odds ratio: 4.9, CI: 1.7-14.2) were independent predictors of coronary artery disease. Conclusions: We have demonstrated a significant relationship between depression and anxiety scores and coronary artery disease while cardiovascular risk factors were similar for both groups.
Keywords: coronary artery disease; anxiety; depression; MYOCARDIAL-INFARCTION; HEART-DISEASE; MORTALITY RISK; SYMPTOMS; ASSOCIATION; MECHANISMS; ISCHEMIA; STRESS; TRIAL; MEN